Pushing down the limit: in vitro detection of a polypeptide monolayer on a single infrared resonant nanoantenna - Semenyshyn, Rostyslav; Mörz, Florian; Steinle, Tobias; Ubl, Monika; Hentschel, Mario; Neubrech, Frank; Giessen, Harald (ACS photonics, 2019)
Infrared vibrational spectroscopy is a powerful tool for the identification of changes of the secondary protein structure, which are associated with many human diseases, such as Alzheimer’s or Parkinson’s disease. In order to obtain deeper insight into the mechanisms that lead to such changes, it is important to investigate the protein conformation on minimum sample concentrations and volumes, ideally on the single-protein level, and at short measurement times. For this purpose, surface-enhanced infrared absorption in combination with Fourier-transform infrared (FTIR) micro-spectroscopy is a highly suitable technique, but is usually limited to large numbers of proteins and long integration times due to the low brilliance of the standard thermal infrared light sources, such as Globar light sources. Here, we push this inherent limit down by using a highly brilliant, broadband mid-IR laser in combination with a standard FTIR microscope. Thus, detecting the secondary protein structure in a sample volume that is ∼100 times smaller than previously demonstrated becomes feasible with our tabletop FTIR system. We utilize polypeptides as a model system, which we functionalize on a single resonant gold nanoantenna, and demonstrate the capabilities of our ultrasensitive system to detect the protein conformation in a living environment within 10 min, without the necessity of frequency tuning the mid-IR laser or any data postprocessing. For comparison, measurements conducted with a synchrotron light source were also performed, which support the results obtained with the laser source. We believe that with further advances it will be possible to scale the process to the ultimate limit of a few or even single proteins and observe the conformational behavior of a few or individual entities in an aqueous environment.
Gesehen am 10.01.2020